Behaviour of hybrid concrete columns under axial compression loads - Resheq Ali (MATEC Web of Conferences, 2018)
Hybrid Concrete Column (HCC) is composite column consists of two types of concrete, Normal Concrete (NC) and Self Compacted Concrete (SCC). The main objective of this work is to study the effect of outer to inner diameter ratio of hybrid concrete on the ultimate strength of column under the axial loading. Ten scaled columns (150 mm diameter and 600 mm length) were fabricated and cast with different ratio of NC to SCC and tested under axial loading. The test results were presented in term of loading and the axial and lateral strains at mid span of column length. It was found that the ultimate strength of column increased from 281 kN to 605 kN (215%). Also it was found that the strength of column increased when the SCC is in inner thickness rather than in outer thickness of the column and the strength increased with increasing the inner thickness of SCC.